The effect of media coverage on target firms’ trading activity and liquidity around domestic acquisition announcements: evidence from UK - Gorman, Louise (2021)
This study investigates the effect of news media coverage on trading activity in, and the liquidity of, target firms’ shares around acquisition announcements. We use the number of articles published in four of the UK's main newspapers as a proxy for media coverage. Our dataset includes 350 UK domestic acquisition deals between 1996 and 2014. The results of our analysis suggest that media coverage is positively associated with target firms’ trading activity and stock liquidity. This is consistent with the media playing a key role in mitigating information asymmetry in the financial markets. This study contributes to the literature on stock market reactions to acquisition announcements by investigating the effect of media coverage on trading activity and stock liquidity beyond the price run-up, and by providing additional insights into the UK market which traditionally attracts less attention than the US market.